Effect of Support for Entrepreneurship Development on Economic Growth and Development in Nigeria - Adelekan, Saidi Adedeji; Tijani, Abideen adekunle (European Scientific Journal, ESJ, 2017)
This paper examines the effect of support for entrepreneurship development on economic growth and development in Nigeria with a view to ameliorating some problems militating against the development of Nigeria. Secondary data was sourced from CBN reports, NBS reports and so on. Hypotheses were set and tested by engaging the linear regression method as the analytical tool. The results discovered that government policy has helped in developing entrepreneurs’ skill in Nigeria and that whatever polices formulated in the time past has not helped in the development of entrepreneurial skill. In light of these, it was recommended that policies of entrepreneur development and the delivery institutions must be appropriate so that the small industrial units that are being promoted do not fall into a peculiar and complex difficulty.